2002
DOI: 10.1002/cncr.10330
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between positron emission tomography and computed tomography in the use of the assessment of esophageal carcinoma

Abstract: Struggling with nature is certainly a familiar feeling to many of us. This particular metaphor began life, however, after another wrestling bout, in a striking classical allusion by Francis Bacon in 1605. We trace the evolution of the metaphor through the centuries and the way it has been invoked in opposition to science. Is it possible to experiment without intrusion?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
100
1
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(110 citation statements)
references
References 25 publications
(38 reference statements)
5
100
1
4
Order By: Relevance
“…18 F-FDG PET/CT is a metabolic imaging method and its usefulness in esophageal cancer patients has been reported in several studies (9,10,11,12). SUV has been widely used parameter for evaluation of FDG uptake degree of several tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…18 F-FDG PET/CT is a metabolic imaging method and its usefulness in esophageal cancer patients has been reported in several studies (9,10,11,12). SUV has been widely used parameter for evaluation of FDG uptake degree of several tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…As for ESCC, a markedly increased FDG uptake has been documented previously [22,23,24,25,26], and PET is rapidly developing into a noninvasive method for preoperative staging. However, the impact of PET on the detection of locoregional lymph node (LN) metastasis is still unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, most studies (12 of 15) showed that pretreatment FDG uptake is a predictor for survival in univariate analysis, whereas only 2 studies showed FDG uptake to be a predictor of survival in multivariate analysis 30–33,35,36,39,43,44,53,55,56. More importantly, neither of the 2 largest prospective trials could prove the prognostic significance of FDG-PET 52,56…”
Section: Resultsmentioning
confidence: 99%
“…3044,52–56 In the second group, 6 studies described decrease in FDG uptake measured early during neoadjuvant therapy (group 2A: Table 3), and also 10 studies described decrease in FDG uptake measured after completion of neoadjuvant therapy (group 2B: Table 3). 14,16,38,41,42,4551,55,5759 Also, 9 studies described the same cohorts of patients; however these were not excluded 31,32,35,36,41,42,47,49,51. Methodological aspects of included studies are described in Tables 4, 5, and 6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation